2015
DOI: 10.1097/inf.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Prevalence in Routine Bloodstream Isolates from Children’s Hospitals Varies Substantially from Adult Surveillance Data in Europe

Abstract: Age-stratified presentation of resistance percentage estimates by surveillance programs will allow identification of important variations in resistance patterns between different patient groups for targeted intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 20 publications
7
43
2
5
Order By: Relevance
“…The Antibiotic Resistance and Prescribing in European Children project which included 392 GN infections in children below 1 year of age from 12 European countries, reported higher rates of aminoglycoside and third generation cephalosporin resistance for Klebsiella spp and similar rates of gentamicin, third generation cephalosporin, ciprofloxacin and carbapenem resistance for E. coli infections19 compared with our cohort. Lutsar et al 20 also reported significantly higher rates of resistance for enterobacteriaceae (ranging from 10% for meropenem to 40% for piperacillin–tazobactam) in a smaller cohort of 24 infants from NNUs across five European countries and a 17% infection-related mortality.…”
Section: Discussionmentioning
confidence: 48%
“…The Antibiotic Resistance and Prescribing in European Children project which included 392 GN infections in children below 1 year of age from 12 European countries, reported higher rates of aminoglycoside and third generation cephalosporin resistance for Klebsiella spp and similar rates of gentamicin, third generation cephalosporin, ciprofloxacin and carbapenem resistance for E. coli infections19 compared with our cohort. Lutsar et al 20 also reported significantly higher rates of resistance for enterobacteriaceae (ranging from 10% for meropenem to 40% for piperacillin–tazobactam) in a smaller cohort of 24 infants from NNUs across five European countries and a 17% infection-related mortality.…”
Section: Discussionmentioning
confidence: 48%
“…The actual percentages of MDR-GNB reported in this study should be interpreted with caution, as hospitals reporting to ARPEC were tertiary institutions with a patient population not representative of patients in other inpatient settings and potentially at higher risk of MDR-GNB [20, 21]. Pooling of data prohibits the identification of any differences between individual participating centres, some of which may have had higher or lower than average MDR-GNB percentages.…”
Section: Discussionmentioning
confidence: 98%
“…The study used data from the ARPEC project, which was co-funded by the European Commission DG Sanco through the Executive Agency for Health and Consumers [20, 21]. …”
Section: Methodsmentioning
confidence: 99%
“…In patients with such risk factors (eg, known colonisation by extended-spectrum β-lactamase producing bacteria) the treating physician may feel that a very broad regimen, such as meropenem, is a safe bet. Even the broadest antibiotic regimens, however, have gaps in their cover: K. pneumoniae bloodstream isolate resistance to carbapenems is known to be around 7% in children across Europe 10. This means that one would have to use ever more complicated combination regimens to ensure that all possible isolates, including carbapenem-resistant Enterobacteriaceae, are covered.…”
Section: Should This Patient Be Treated With a Carbapenem Empirically?mentioning
confidence: 99%
“…Another limitation is that antibiograms are rarely age-specific, even though pathogen and resistance patterns for children and adults are not the same 10 12. Consequently, to support empirical antibiotic prescribing, clinicians require a summary statistic that will describe the likely overall cover of different antibiotic regimens given the type of patient and infection.…”
Section: What Tools Can Support Empirical Antibiotic Decisions?mentioning
confidence: 99%